2020
DOI: 10.1039/d0nj00209g
|View full text |Cite
|
Sign up to set email alerts
|

An anthracene-pendant ruthenium(ii) complex conjugated to a biotin anchor, an essential handle for photo-induced anti-cancer activity

Abstract: Efficient avidin binding and selective cancer cell response upon light irradiation of an enhanced ROS photogenerator biotinylated ruthenium complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…1 O 2 has a very short lifetime (μs) and diffusion coefficient, and it is not neutralized by any naturally occurring enzyme inside the cells. 29,30 To understand the cell death mechanism in PDT and the efficiency of PSs, the investigation of efficient photoproduction of 1 O 2 is important. Herein, the evaluation of the 1 O 2 generation efficacy of the complexes 1–3 was carried out in DMF using photooxidation of 1,3-diphenylisobenzofuran (DPBF) by recording its time-dependent absorbance A 415 nm in the dark and upon photoirradiation.…”
Section: Resultsmentioning
confidence: 99%
“…1 O 2 has a very short lifetime (μs) and diffusion coefficient, and it is not neutralized by any naturally occurring enzyme inside the cells. 29,30 To understand the cell death mechanism in PDT and the efficiency of PSs, the investigation of efficient photoproduction of 1 O 2 is important. Herein, the evaluation of the 1 O 2 generation efficacy of the complexes 1–3 was carried out in DMF using photooxidation of 1,3-diphenylisobenzofuran (DPBF) by recording its time-dependent absorbance A 415 nm in the dark and upon photoirradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the promising chemical properties of this compound as the ROS generator can still be further explored as a potential drug by designing modifications to improve hydrophobicity and or using a delivery platform to achieve cell targets. 31,58,59 In this work, we showed that a mimic of the anthracycline drug, upon binding to iron, can produce deleterious molecules, which might be associated with multiple undesired side effects caused by this type of compound.…”
Section: Discussionmentioning
confidence: 98%
“…In order to investigate the effect of quinizarin, cis-[Fe(cyclam)Cl 2 ]Cl and [(Fe(cyclam)) 2 (Qz)] Cl(PF 6 ) 3 on the cell viability, the MTS assay was carried out as previously described. 31 After trypsinization from T-25 flasks, cells (1.0 Â 10 4 /200 mL per well) were seeded in 96-well flat bottom plates. Different concentrations of the tested compounds (100-1.58 mg mL À1 ) were dissolved in DMSO and then added to the wells.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…In the last few decades, biotin has attracted tremendous importance among the scientific and pharmaceutical communities and has been used as a small target-specific moiety for cancer cells, drug monitoring, and therapy due to its low molecular weight, high tumor specificity, and most importantly biocompatibility . Nevertheless, a few PSs like phthalocyanine, , porphyrin, chlorins, , nile blue, ruthenium metal complexes, , and iron­(III) metal complexes have been conjugated with biotin for targeted PDT. Biotin has also been conjugated with aza-BODIPYs; however, this was limited particularly for drug monitoring and bioimaging studies .…”
Section: Introductionmentioning
confidence: 99%